A novel UV‐curable epoxy acrylate resin containing arylene ether sulfone linkages: Preparation, characterization, and properties. Issue 22 (13th June 2014) - Cui, Jidi; Yu, Guipeng; Pan, Chunyue
ABSTRACT UV‐curing processes are used in industrial applications because of their advantages such as high‐speed applications and solvent‐free formulations at ambient temperature. UV‐curable epoxy acrylate resins containing arylene ether sulfone linkages (EAAES) were synthesized through the condensation of bis(4‐chlorophenyl)sulphone and bisphenol‐A, followed by end‐caping of epichlorohydrin and subsequently acrylic acid. UV‐cured coatings were formulated with epoxy acrylates, reactive diluents such as pentaerythritol tri‐acrylate and pentaerythritol dia‐crylate and photoinitiator. Fourier transfer infrared, 1H NMR, and thermal gravimetrical analysis were employed to investigate the structures and thermal properties of the EAs films. The introduction of EAAES into epoxy acrylate substantially improves its thermal properties and thermo‐oxidative stability at high temperatures. In addition, the acrylate containing arylene ether sulfone linkages can also improve pencil hardness and chemical and solvent resistance of the epoxy acrylate. The obtained UV‐curable epoxy acrylate containing arylene ether sulfone linkages is promising as oligomer for UV‐curable coatings, inks, and adhesives in some high‐tech regions. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41067.